The Role of Women in Islamic Sacred Texts: A Critical Study of Women's Narratives and Authority in Islamic Tradition - Intan Erwani; Anisa Suryani Siregar (Pharos Journal of Theology)
This research aims to examine the role and authority of women in Islamic sacred texts, focusing on narratives within the Quran and Hadith and their implications for the social status and leadership of women in contemporary religious contexts. The urgency of this study stems from a significant discrepancy between women's representation in Islamic doctrine and their participation and recognition in broader religious and social power structures. Employing a qualitative methodology with a phenomenological approach, this study collected data from primary sources through in-depth interviews, as well as document analysis and secondary literature review, to explore interpretations of texts and prevailing practices. The findings reveal that although the sacred texts provide a basis for gender equality, traditional interpretations often restrict women's roles in leadership and authority capacities. Discussions on reinterpreting these texts with a more inclusive gender perspective offer opportunities to expand understandings of women's leadership in Islam. This study also highlights the importance of education in supporting women to take on more active roles in religious activities and leadership. Based on these findings, the research recommends adopting a more egalitarian interpretative approach in Islamic theology and integrating gender-inclusive religious education as strategies to overcome structural and social barriers that hinder women. These recommendations aim to encourage broader dialogue and fairer religious practices, supporting social change that recognises and promotes women's roles and authority in Muslim communities.